ANALISIS MEKANISME PEMBIAYAAN MURABAHAH AL-WAKALAH PADA PRODUK TANGGUNG RENTENG DI PT. BPRS HAJI MISKIN PANDAI SIKEK DITINJAU DARI KETENTUAN OJK DAN FATWA DSN-MUI - Rahmad Suganda; Yefri Joni (Jurnal Ekonomi dan Bisnis, 2025)
This research aims to analyze why the murabahah al wakalah financing mechanism for joint responsibility products at PT. BPRS Haji Miskin Pandai Sikek is not in accordance with OJK provisions and the DSN-MUI fatwa, apart from analyzing the reasons why PT. BPRS Haji Miskin Pandai Sikek uses the murabahah al-wakalah agreement on joint responsibility products. Apart from the qualitative descriptive research approach, field research is the research methodology used in this research. Data was collected using three different techniques: observation, interviews, and documentation. Meanwhile, the data analysis techniques used are data reduction, data presentation, and drawing conclusions. Research findings show that certain aspects have not been implemented, such as parallel or simultaneous implementation of murabahah and wakalah contracts, where in theory the bank does not own the goods at the time the contract is executed. The first provision point (i) is the guidebook for sharia banking murabahah financing products issued based on OJK and DSN-MUI fatwa no. 04 of 2000 concerning murabahah, refers to the murabahah financing scheme with a Purchase Promise (Wa'd) accompanied by Wakalah. It is stated that if the bank wants to represent the customer to buy goods from a third party, so that the murabahah sale and purchase contract officially becomes the property of the bank, then the product needs to be implemented. The use of a murabahah al wakalah contract makes sense because it can facilitate transactions for both the bank and the customer.